Molecular Mechanisms of Glutamate Toxicity in Parkinson’s Disease - Wang, Ji; Wang, Fushun; Mai, Dongmei; Qu, Shaogang (Frontiers in Neuroscience, 2020)
Parkinson’s disease (PD) is a common neurodegenerative disease, the pathological features of which include the presence of Lewy bodies and the neurodegeneration of dopaminergic neurons in the substantia nigra pars compacta. However, until recently, research on the pathogenesis and treatment of PD have progressed slowly. Glutamate and dopamine are both important central neurotransmitters in mammals. A lack of enzymatic decomposition of extracellular glutamate results in glutamate accumulating at synapses, which is mainly absorbed by excitatory amino acid transporters (EAATs). Glutamate exerts its physiological effects by binding to and activating ligand-gated ion channels (ionotropic glutamate receptors, iGluRs) and a class of G-protein-coupled receptors (metabotropic glutamate receptors, mGluRs). Timely clearance of glutamate from the synaptic cleft is necessary because high levels of extracellular glutamate overactivate glutamate receptors, resulting in excitotoxic effects in the central nervous system. Additionally, increased concentrations of extracellular glutamate inhibit cystine uptake, leading to glutathione depletion and oxidative glutamate toxicity. Studies have shown that oxidative glutamate toxicity in neurons lacking functional N-methyl-D-aspartate (NMDA) receptors may represent a component of the cellular death pathway induced by excitotoxicity. The association between inflammation and excitotoxicity (i.e., immunoexcitotoxicity) has received increased attention in recent years. Glial activation induces neuroinflammation and can stimulate excessive release of glutamate, which can induce excitotoxicity and, additionally, further exacerbate neuroinflammation. Glutamate, as an important central neurotransmitter, is closely related to the occurrence and development of PD. In this review, we discuss recent progress on elucidating glutamate as a relevant neurotransmitter in PD. Additionally, we summarize the relationship and commonality among glutamate excitotoxicity, oxidative toxicity, and immunoexcitotoxicity in order to posit a holistic view and molecular mechanism of glutamate toxicity in PD.